Thermoplastic polymers in the production of plywood products: advantages, opportunities and perspectives for application - Pavlo Bekhta; Iryna Kusniak (Наукові праці Лісівничої академії наук України, 2018)
One of the main adhesives used in the production of plywood are urea – and phenol-formaldehyde adhesives. In spite of their many positive charac-teristics such adhesives are toxic. Previous studies have proved that the for-maldehyde giving off can cause the respiratory, nervous system and eyes damage and even cancer and leukemia. The World Health Organization has also recently concluded that formaldehyde is a human carcinogen. Therefore, the wood materials toxicity reduction has great importance for the environment and especially for human health. Throughout recent years, requirements to the products that a person contacts, as well as those materials used for their manufacture, have increased. Scientists were faced with the question of finding new adhesives which could replace existing toxic synthetic thermosetting glues on the new non-toxic glues. Attempts to make plywood based on natural glues were done – proteins (casein), bone collagen, skin and fining, albumin, carbohydrates (on the basis of starch or its derivative – dextrin), natural latex and rubber glues. However, due to low water or biodegradability, low heat resistance, lack of some types of raw materials for their production and also necessity to save food raw materials nowadays they do not find large-scale application in wood composite materials production. After several researches, the possibility of gluing plywood with synthetic thermoplastic polymers, the melting point of which does not exceed 200 oC were proposed. Many scientists studied the question of plywood production based on the thermoplastic polymers. In particular the plywood production with the use of thermoplastic films was proposed. In this review the advantages, possibilities and perspectives of the thermoplastic polymers using for the plywood products production are analyzed. One of the main advantages of such polymers is their non-toxicity. Surface treatment of the plywood with polymeric films based on polyeth-ylene and polypropylene is considered. In addition, an accelerating aging impact of the plywood surface covered with polyethylene and polypropylene films on its properties is found out. Polyethylene and polypropylene have low adhesion to the wood. The adhesion increasing possibilities between thermoplastic polymers and veneer / plywood by chemical and thermal modification of both polymers and veneer are analyzed. The possibility of the thermoplastic polymers waste using in the plywood production, the retreatment of which will reduce the cost of the primary polymer and will solve the problem of the environmental protection is considered as well. In general, low cost and environmental indicators jointly open the wide opportunities of using thermoplastic polymers in plywood production.